H. Asnawi Mangku Alam: Pemikiran dan Pengabdiannya Di Sumatera Selatan Tahun 1921-2001 - Mubaroq, Vixkri (Tanjak: Sejarah dan Peradaban Islam, 2020)
This paper is entitled about H. Asnawi Mangku Alam's Thought and Devotion in South Sumatra in 1921-2001. In this paper, he explains the biography of social life, environment and education, as well as the thoughts and dedication of the figure H. Asnawi Mangku Alam. This writing uses the historical method, with heuristic stages, source criticism, interpretation, and historiography. The theory used is the social exchange theory put forward by George Casper Homans and the habitus theory put forward by Pierre Bourdieu. H. Asnawi Mangku Alam is a local figure from South Sumatra who made a big contribution to independence. After studying, he devoted himself to being actively involved in the military field and playing a role in the struggle to defend Indonesia's independence in the Palembang and Komering regions in 1947. As well as being a governor, Asnawi Mangku Alam was also the Ambassador for Burma and Nepal. The author describes three areas of contribution from the thought of H. Asnawi Mangku Alam when he was appointed governor of South Sumatra in 1968-1978, namely the fields of religion, economy and politics. As for some of the writings of H. Asnawi Mangku Alam and then the writer made the source in writing. Among them are a collection of Da'wah, a collection of sermons, a farmer's son to become a governor, a 120 hour city war in Palembang, Padamu Lies Laitaul Qadar, Cita and Karya, as well as messages and impressions.